Methods in Lung Microbiome Research - Carney, Sharon M.; Clemente, Jose C.; Cox, Michael J.; Dickson, Robert P.; Huang, Yvonne J.; Kitsios, Georgios D.; Kloepfer, Kirsten M.; Leung, Janice M.; LeVan, Tricia D.; Molyneaux, Philip L.; Moore, Bethany B.; O’Dwyer, David N.; et al. (American journal of respiratory cell and molecular biology, 2020)
The lung microbiome is associated with host immune response and health outcomes in experimental models and patient cohorts. Lung microbiome research is increasing in volume and scope; however, there are no established guidelines for study design, conduct, and reporting of lung microbiome studies. Standardized approaches to yield reliable and reproducible data that can be synthesized across studies will ultimately improve the scientific rigor and impact of published work and greatly benefit microbiome research. In this review, we identify and address several key elements of microbiome research: conceptual modeling and hypothesis framing; study design; experimental methodology and pitfalls; data analysis; and reporting considerations. Finally, we explore possible future directions and research opportunities. Our goal is to aid investigators who are interested in this burgeoning research area and hopefully provide the foundation for formulating consensus approaches in lung microbiome research.